Reconstructing Westphalian Sovereignty as an Effort to Enforce Human Rights Case Study: Humanitarian Intervention in the Libyan Conflict - Mubin, Anna Kharisma Fehmita (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
State sovereignty and humanitarian intervention are two sides of a coin, presenting a threat to human rights enforcement, especially when human rights violation is done by the state. Failure from a state to provide human rights protection for its citizen will lead to intervention from the international community to enforce human rights in the name of humanitarian norms. The humanitarian intervention will indirectly weaken the principles of Westphalian state sovereignty as the main premise in the politics of international relations. This article is a case study of the Libyan conflict in 2011. This study uses the constructivism approach to analyze the contrasting relation between the principles of traditional Westphalian sovereignty and humanitarian intervention concept, and how this relationship may shift the human rights norms in the international community. In the constructivism approach, it is not enough to offer a causal explanation in order to understand international politics. Instead, it needs a more interpretative understanding. Hence, this study is conducted with a qualitative method, a critical approach to human rights in contemporary international politics.